2011
DOI: 10.1186/cc10489
|View full text |Cite
|
Sign up to set email alerts
|

Presence of tobramycin in blood and urine during selective decontamination of the digestive tract in critically ill patients, a prospective cohort study

Abstract: IntroductionTobramycin is one of the components used for selective decontamination of the digestive tract (SDD), applied to prevent colonization and subsequent infections in critically ill patients. Tobramycin is administered in the oropharynx and gastrointestinal tract and is normally not absorbed. However, critical illness may convey gut barrier failure. The aim of the study was to assess the prevalence and amount of tobramycin leakage from the gut into the blood, to quantify tobramycin excretion in urine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Selective decontamination of the digestive tract (SDD) prophylaxis of BT, which prevents the overgrowth of pathogens by enteral co-administration of non-absorbable antibiotics, such as colistin, tobramycin, amphotericin B, and vancomycin (VCM) (Benus et al 2010 ; Cerdá et al 2007 ; Roos et al 2011 ) has been previously reported. It has been shown that any absorption of the non-absorbable antibiotic in the SDD regimen can be considered negligible under “normal conditions”; however, significant absorption of tobramycin was reported in critically ill patients (Oudemans-van Straaten et al 2011 ), as was VCM in patients with chemotherapy-associated and/or Clostridium difficile colitis (Aradhyula et al 2006 ; Bergeron and Boucher 1994 ). In addition, we previously reported the enhanced intestinal permeability of a hydrophilic dye, phenolsulfonphthalein, in PN-induced intestinal atrophy (Fukushima et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Selective decontamination of the digestive tract (SDD) prophylaxis of BT, which prevents the overgrowth of pathogens by enteral co-administration of non-absorbable antibiotics, such as colistin, tobramycin, amphotericin B, and vancomycin (VCM) (Benus et al 2010 ; Cerdá et al 2007 ; Roos et al 2011 ) has been previously reported. It has been shown that any absorption of the non-absorbable antibiotic in the SDD regimen can be considered negligible under “normal conditions”; however, significant absorption of tobramycin was reported in critically ill patients (Oudemans-van Straaten et al 2011 ), as was VCM in patients with chemotherapy-associated and/or Clostridium difficile colitis (Aradhyula et al 2006 ; Bergeron and Boucher 1994 ). In addition, we previously reported the enhanced intestinal permeability of a hydrophilic dye, phenolsulfonphthalein, in PN-induced intestinal atrophy (Fukushima et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oudemans‐van Straaten et al. used HPLC–MS/MS assay for the determination of tobramycin concentration in serum and urine. The experimental conditions for the analyses of some AKI biomarkers in plasma and urine of human beings and rats are summarized in Tables and , respectively.…”
Section: Analyses Of Acute Kidney Injury Biomarkersmentioning
confidence: 99%
“…If the gut barrier is intact, the antibiotics exert their effect in the digestive tract and are not absorbed. However, conditions such as sepsis, shock, and major surgery can lead to gut barrier failure [54] and may result in the antibiotics leaking from the gut into the blood.…”
Section: Current Practice Procedures For the Management Of Intra-abdomentioning
confidence: 99%